Genome-wide identification and functional characterization of the KWL gene family in three Oryza species - Wu, Lyu; Liu, Wei; Xin, Guimin; Chen, Yang; Zhou, Haitao (Frontiers in Plant Science, 2025)
IntroductionThe Kiwellin (KWL) gene family, although previously implicated in plant stress responses, remains poorly characterized in rice. This study aims to perform a comprehensive genome-wide analysis of the KWL family across three rice species to elucidate their roles.MethodsWe analyzed the KWL family in Oryza sativa ssp. japonica (Os), O. sativa ssp. indica (Osi), and O. rufipogon (Or). Systematic analyses of their phylogeny, gene structures, conserved motifs, chromosomal localization, and promoter cis-elements were performed. The expression patterns of key genes in response to phytohormones were validated, and their subcellular localization and transcriptional activity were experimentally determined.ResultsA total of 33 KWL genes were identified (9 in Os, 12 in Osi, and 12 in Or). Phylogenetic analysis revealed that KWL proteins were highly conserved within rice species but distinct from their maize and tomato orthologs. Promoter cis-element analysis revealed a significant enrichment of elements associated with biotic/abiotic stress responses and phytohormone signaling. Expression profiling demonstrated that most family members exhibited low or tissue-specific expression, with OsKWL1 and OsKWL2 exhibiting marked responsiveness to ABA and JA treatments in roots and shoots, respectively. Subcellular localization experiments confirmed that both OsKWL1 and OsKWL2 proteins were localized to the cytoplasm. Furthermore, yeast assays revealed that OsKWL1 possessed strong autoactivation activity.ConclusionThis study establishes a foundational framework for future functional investigations of the KWL family in rice, highlighting its potential roles in stress adaptation.